Internet adoption by rapidly internationalising SMEs: a further challenge to staged e-adoption models. (16th April 2007) - Loane, Sharon; Bell, Jim; Deans, Kenneth R.
There has been considerable recent interest in the literature on the impact of the internet on the internationalisation processes of SMEs. This contribution reports the findings of a four-country study on how internationalising Australian, Canadian, Irish and New Zealand firms utilise the internet. The findings suggest that SMEs in all countries use it extensively for communication purposes and make fairly widespread use of the internet for business processes, marketing and product development purposes, competitor analysis and market intelligence gathering. However, low usage is found in terms of online transactions and supply chain management. From these results, the authors conclude that many rapidly internationalising SMEs do not follow 'stages' of internet adoption suggested by many of the extant e-adoption models.